The Effectiveness of Science Learning Media Using Focusky Software on Junior High School Students’ Higher Order Thinking Skills - Agnesi Sekarsari Putri; Nurfina Aznam (Scientiae Educatia: Jurnal Pendidikan Sains, 2019)
This research aimed to identify the effectiveness of science learning media using focusky software on junior high school students’ High Order Thinking Skill (HOTS). Quasi-experiment is applied in pre-test – post-test non-equivalent control group design. The sampling technique applied wass cluster random sampling. Meanwhile, the instrument used was HOTS pre-test – post-test question. Data analysis techniques used were normality test, homogeneity test, Paired Sample T-test, Independent Sample T-test, and effect size. The result of this study indicates that the increase in HOTS of students in the experimental class was 50. It is higher than in the control class, which was only 30. The average post-test of the experimental class was 75.90, with 87% of students achieving the minimum criterion, while the average post-test of the control class was 60.25, with 75 % of students reach the minimum criterion. Based on the result of the Independent Sample T-test, it was shown that there were differences in HOTS abilities between the experimental class students and the control class students, and the effectiveness of the medium-sized learning media assisted by science learning media with an effect size of 0.7.